Broadening Perspectives on Immigrant Experiences: Secondary Students Study the Absorption Difficulties Faced by Mizrachi Immigrants in Israel. Issue 3 (3rd July 2018) - Reingold, Matt
ABSTRACT: Over the course of the 2015–2016 academic year, 12th-grade students at a Jewish high school in Canada participated in a research study that assessed how they integrated morally complex narratives in Israel's past into their own relationship with the country. This article presents material based on how students reacted to learning that some Jewish immigrants were mistreated by the government by way of intentional economic disparity, depiction as grotesque caricatures in standard curricula, and denial of access to funds for cultural expression. The majority of students expressed shock and outrage as this narrative contrasted with the Zionist narrative that they had previously learned.